Case Report: Immune checkpoint inhibitor exhibits dual benefits for a refractory lymphoma patient with disseminated mucormycosis - Teng, Qibei; Yang, Qianqian; Tao, Zhizhi; Huang, Jinwen; Zhang, Cheng; Shao, Fangfei; Pan, Wenjue; Zhao, Xiujie; Xiao, Haowen (Frontiers in Medicine, 2025)
Invasive mucormycosis contributes to a high mortality rate in patients with hematological malignancies. When it disseminates to multiple organs, especially to the brain, the prognosis is extremely poor. The traditional antifungal strategies including surgery have less efficacy in patients with hematological malignancies. Here, we describe a case report of a 62-year-old man with refractory lymphoma who developed mucormycosis caused by Rhizomucor pusillus after chemotherapy, which disseminated extensively to the lungs, diaphragm, brain and spleen. He was successfully treated with antifungal agents combined with PD-1 inhibitor, which may simultaneously exhibit efficacy in treatment of lymphoma and mucormycosis. The patient’s lymphoma and mucormycosis were well controlled; ultimately, autologous hematopoietic stem cell transplantation was successfully performed, and the patient achieved long-term survival.